Users in water management - Hooja, Rakesh.(ed.) (Jaipur, 2002)
This volume puts together some of the best research studies on the PIM programme being implemented in Andhra Pradesh. These give an insight into the political processes behind the reforms, the adminis trative, institutional and management issues, and finally based on the analysis the way forward for the programme in Andhra Pradesh and a cumulative learning experi ence for other states in India and the world to incorporate and implement. Comparison with states like Madhya Pradesh, Karnataka and Gujarat have also been made. The book has not only tackled theoretical issues and concepts but also practical ground level realities regarding PIM.
Keywords: Water management-Andhra Pradesh